The Impact of Inclusive Education on School Performance: Managerial Perspectives and Financial Outcomes - Tukan, Gita Maria Magdalena; Susandi, Deny Gunawan (CV. Ulil Albab Corp, 2025)
This study investigates the impact of inclusive education on school performance from managerial and financial perspectives in three public schools in South Tangerang, Indonesia. Using a mixed-methods approach, the research combines quantitative data from surveys and budget documents with qualitative insights from interviews with school leaders. Quantitative findings indicate a positive correlation between budget allocation for inclusive programs and improvements in student engagement and dropout rates. However, inconsistencies in funding distribution and limitations in budget autonomy hinder the full realization of inclusive goals. Qualitative data reveal that school administrators are committed to inclusive values but face systemic constraints in aligning policy with practice. Leadership strategies such as collaborative decision-making and shared responsibility were commonly adopted, although challenges remain in data utilization and financial planning. The study concludes that inclusive education requires not only adequate and predictable funding but also managerial capacity and institutional flexibility. Effective inclusion depends on the interplay between financial investment, leadership responsiveness, and data-informed governance. These findings have important implications for policymakers seeking to strengthen inclusive education through sustainable financial models and leadership development initiatives.